Supercritical water oxidation of wastewater from acrylonitrile manufacturing plant - Shin, Young Ho; Shin, Nae Chul; Veriansyah, Bambang; Kim, Jaehoon; Lee, Youn-Woo (ELSEVIER SCIENCE BV, 2009)
The wastewater from an acrylonitrile manufacturing plant, which is difficult to biodegrade, was decomposed in subcritical and supercritical water. Experiments were carried out at temperature ranging from 299 to 552 degrees C and a pressure of 25 MPa. The initial total organic carbon (TOC) of acrylonitrile wastewater was set from 0.27 to 2.10 mol L-1 with residence times ranging from 3 to 30 s. 30 wt.% H2O2 Solution was used as an oxidant with the stoichiometric ratios Of O-2 based on the initial TOC concentration ranging from 0.5 to 2.5. TOC conversion increased with increasing reaction temperature and residence time, however, beyond the stoichiometric oxygen-TOC ratio of 1:1, TOC conversion was barely affected by excess oxygen. The initial TOC concentration of acrylonitrile wastewater also had a negligible effect on TOC conversion. An assumed pseudo-first-order global rate expression was determined with an activation energy of 53.48(+/-33.57) kJ mol(-1) and a pre-exponential factor of 5.22(+/-1.74) x 10(2) s(-1). By considering the dependence of the reaction rate on TOC and O-2 concentration, a global rate expression was regressed from the complete set of 64 data points. The resulting activation energy was 66.33(+/-5.87) kJ mol(-1); the pre-exponential factor was 6.07(+/-6.89) x 10(3) mol(-0.26) s(-1): and the reaction orders for initial TOC and O-2 concentration were 1.26(+/-0.15) and 0.00(+/-0.15), respectively. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: REACTOR; SCWO; DESTRUCTION; SALT